2021
DOI: 10.20450/mjcce.2021.2417
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive components and antioxidant, antiproliferative, and antihyperglycemic activities of wild cornelian cherry (Cornus mas l.)

Abstract: The contents of polyphenolic components (total polyphenols, flavonoids, and monomeric anthocyanins) and vitamin C, and the bioactive potential (antioxidant, antiproliferative, and antihyperglycemic activities) of wild cornelian cherry were determined. Samples were collected from four different locations in Bosnia and Herzegovina. Sample CC3 from Drinić had the highest monomeric anthocyanin content (1.40 mg CyGE/g FW) and the highest inhibition of free radicals (IC50 DPPH = 262.19 mg/ml; IC50 ABTS = 76.78 mg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Odžaković et al [ 45 ] performed several tests, such as DPPH, ABTS, and OH radical neutralization, to determine the antioxidant capacity of several ecotypes of cornelian cherry growing in various regions of Bosnia and Herzegovina ( Table 1 ). Ecotype CC3 from the Drinić area featured the highest level of monomeric anthocyanins (1.40 mg CyGE·g −1 FW) and the highest capacity of inhibiting free radicals (IC50 DPPH = 262.19 mg·mL −1 ; IC50 ABTS = 76.78 mg·mL −1 ; IC50 OH ˙ = 102.31 mg·mL −1 ).…”
Section: Health-promotion Effects Of Anthocyanins Derived From Cornel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Odžaković et al [ 45 ] performed several tests, such as DPPH, ABTS, and OH radical neutralization, to determine the antioxidant capacity of several ecotypes of cornelian cherry growing in various regions of Bosnia and Herzegovina ( Table 1 ). Ecotype CC3 from the Drinić area featured the highest level of monomeric anthocyanins (1.40 mg CyGE·g −1 FW) and the highest capacity of inhibiting free radicals (IC50 DPPH = 262.19 mg·mL −1 ; IC50 ABTS = 76.78 mg·mL −1 ; IC50 OH ˙ = 102.31 mg·mL −1 ).…”
Section: Health-promotion Effects Of Anthocyanins Derived From Cornel...mentioning
confidence: 99%
“…Odzankovic et al [ 45 ] examined the antiproliferative properties of extracts from four cornelian cherry ecotypes growing in Bosnia and Herzegovina. Extracts from cornelian cherry with the highest content of monomeric anthocyanins (CC3) and the highest total polyphenol content (CC4) featured the highest capability of inhibiting cell line growth of breast adenocarcinoma, cervical squamous cell carcinoma, and lung adenocarcinoma ( Table 1 ).…”
Section: Health-promotion Effects Of Anthocyanins Derived From Cornel...mentioning
confidence: 99%
“…The total polyphenol content (TPC) of T. montanum extracts was determined in accordance with Odžaković et al [44] by the Folin-Ciocalteu method. The content of polyphenolic compounds was determined by measuring the absorbance with a UV-vis spectrophotometer (Lambda 25, PerkinElmer, Shelton, CT, USA), and the results were expressed as mg of gallic acid equivalent per gram of dry extract (mg GAE/g DW).…”
Section: Determination Of Total Polyphenol and Flavonoid Contentmentioning
confidence: 99%
“…In another study, the total polyphenol content was determined between 200 mg/100g − 600 mg/100g (Kucharska et al 2009). In a study conducted in Bosnia and Herzegovina, the highest total phenolic content was found to be 55.92 mg GAE/g in certain samples of cornelian cherry samples from four different locations (Odžaković et al 2021). In a study conducted to investigate the phenolic compounds in cornelian cherry fruit and the antioxidant capacity of the fruit, the total phenolic content in cornelian cherry fruits was determined as 230.4 mg GAE/100g − 559.8 mg GAE/100g (Güzel 2021).…”
Section: Correlation Between Genotypes and Phenolic Compounds Accordi...mentioning
confidence: 99%
“…In a study examining the total anthocyanin content in fresh cornelian cherry fruit, the total amount of anthocyanin in C. mas fruit was determined as 2.11 mg/g − 2.62 mg/g (Zia and Alibas 2021). In a study conducted in Bosnia and Herzegovina, the highest total anthocyanin content was found to be 1.40 mg/g in certain samples of cornelian cherry samples taken from four different locations(Odžaković et al 2021). In a study aimed at the extraction of bioactive compounds in cornelian cherry, the total monomeric anthocyanin content was determined as 0.65 mg/g(Kutlu et al 2021a).…”
mentioning
confidence: 98%